The Prado Empire (1890-1970): oligarchy or national bourgeoisie? - Portocarrero Suárez, Felipe (1986)
The process of formation, rise and fall of the Prado family-economic group, most probably the one with the greatest economic influence and political power up to 1970, makes up the main argument of this paper. Were the Prado an oligarchic group, or were they representatives of a national burgeoisie? The author pays special attention to economic aspects throughout, in an attempt to answer this question through the quantification and analysis of the material foundation of the enormous influence this group had in the business world. He also endeavours to determine what were its investment priorities, and what kind of transformations their entrepreneurial policies underwent during the eight decades in which they pursued their activities.